Perancangan Sistem Deteksi Dini Keamanan Informasi DISKOMINFO Kabupaten Bandung - Nazar Firman Pratama (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
In the Digital Transformation era, technological developments are developing more rapidly, along with the increasingly intensive use of technology, cyber threats are also increasing with a wide variety of attacks. The emergence of various issues regarding data leakage from various platforms in Indonesia and even the world. This research originated from several cyber security problems or cyber incidents that occurred, so an early detection system is needed to detect and anticipate these attacks. Solutions that can be implemented to monitor all systems and applications are Security Information Event Management (SIEM). The use of the wazuh platform that can implement SIEM and XDR (Extended Detection Response) technology that can collect all log data information from the latest technological environments, such as the use of Cloud Computing, Virtualization, or Container Engine. Based on the results of the SIEM implementation that has been carried out, SIEM technology with the Wazuh platform can provide convenience in monitoring attacks in real time which can provide warnings and threats to the entire system.